2013
DOI: 10.1017/s1368980013000943
|View full text |Cite
|
Sign up to set email alerts
|

Marketing foods to children: a comparison of nutrient content between children's and non-children's products

Abstract: Objective: The predominance of marketing of products high in fat, sugar and/or salt to children has been well documented and implicated in the incidence of obesity. The present study aimed to determine whether foods marketed to children in UK supermarkets are nutritionally similar to the non-children's equivalent, focusing on food categories that may be viewed as healthier options. Design: Nutritional data were collected on yoghurts (n 147), cereal bars (n 145) and ready meals (n 144) from seven major UK super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 29 publications
5
40
3
4
Order By: Relevance
“…Furthermore, while previous studies had not tested whether increased attempts (e.g. more cues) to market to children were associated with decreases in nutritional content, the current study found that this is precisely the case as increases in the number of child-friendly cues were associated with linear increases in sugar content along with linear decreases in select protective nutrition content, like fibre content and protein content (19,20,22,35,36) . This relationship was found when Table 3 Results of multiple regression models testing the effect of child-friendly and nutrition marketing cues on nutritional content for products in the cereal aisle (n 312) sampled from one branch of a regional supermarket chain in the Southeastern USA, data collected from −0·10 ( * ) P < 0·10, *P < 0·05, **P < 0·01, ***P < 0·001.…”
Section: Discussioncontrasting
confidence: 65%
“…Furthermore, while previous studies had not tested whether increased attempts (e.g. more cues) to market to children were associated with decreases in nutritional content, the current study found that this is precisely the case as increases in the number of child-friendly cues were associated with linear increases in sugar content along with linear decreases in select protective nutrition content, like fibre content and protein content (19,20,22,35,36) . This relationship was found when Table 3 Results of multiple regression models testing the effect of child-friendly and nutrition marketing cues on nutritional content for products in the cereal aisle (n 312) sampled from one branch of a regional supermarket chain in the Southeastern USA, data collected from −0·10 ( * ) P < 0·10, *P < 0·05, **P < 0·01, ***P < 0·001.…”
Section: Discussioncontrasting
confidence: 65%
“…2-9 years); cartoon, television (TV) series or film characters; own-brand characters; child celebrities; images of animals or creatures; games or hobbies; colours or shapes that appeal to children (e.g. brightly coloured drinks or alphabet soup); or free gifts (31,(34)(35)(36) . Two researchers were involved in the identification of products aimed at children.…”
Section: Sampling: Definition Of Food Products Targeted At Childrenmentioning
confidence: 99%
“…A recent review of experimental studies involving children's mascots and licensed characters found high rates of recognition for popular characters and a greater likelihood of choosing foods presented with familiar characters (3) . Previous research from several countries has found children's products in supermarkets to be high in sugar and/or fat (4)(5)(6) . Meanwhile, TV advertisements for food during children's programming are often for unhealthy food items (7)(8)(9) .…”
mentioning
confidence: 99%